The League of Matteo Salvini: Fostering and Exporting a Modern Mass-Party Grounded on “Phygital” Activism - Zulianello, Mattia (2021)
The Lega Nord (LN) has undergone a profound process of transformation since 2013, by replacing its historical regionalist populism with a new state-wide populist radical right outlook. However, very little is known about how such transformation impacted its organizational model, particularly the mass-party features that characterized it under its founding leader, Umberto Bossi. This article explores the organizational evolution of the party under Matteo Salvini by means of a qualitative in-depth analysis of 41 semi-structured interviews with representatives of the LN from four regions (Calabria, Emilia-Romagna, Lombardy, and Veneto) and primary documents. It underlines that the LN was turned into a disempowered and politically inactive “bad company,” charged with the task of paying the debts of the old party, while its structure, resources, and personnel were poured into a new state-wide organization called Lega per Salvini Premier (LSP). The LSP has not simply maintained the key features of the mass-party in the LN’s historical strongholds, but also pioneered a modern form of this organizational model grounded on the continuous interaction between digital and physical activism, i.e., “phygital activism,” which boosts the party’s ability to reach out to the electorate by delivering the image that the League is constantly on the ground. The LSP has sought to export this modern interpretation of the mass-party in the South; however, in that area its organizational development remains at an embryonic stage, and the party’s nationalization strategy has so far produced a “quasi-colonial” structure dominated by, and dependent on, the Northern elite.